Acidophiles Fundamentals and Applications - Lin, Jianqiang; Chen, Linxu; Lin, Jianqun (IntechOpen, 2021)
Acidophiles are an important category of microorganisms defined by their ability to withstand and even grow in acidic environments. They are present in terrestrial and marine environments as well as the human body. The diversity, adaptation, and functions of these microorganisms can contribute to the development and application of new biotechnologies for resolving problems of resource exploitation, pollution, and human disease. This book presents breakthroughs and insights into the research on acidophiles. Chapters cover such topics as the two-component system (TCS) in the regulation of the sulfur metabolic process, adaptation mechanisms of acidophiles to low pH, regulation mechanisms and application strategy of quorum sensing in bioleaching bacteria, and Lactobacillus acidophilus and its potential role as a therapeutic for human bone disorders.